Wayfinding in immersive virtual environments as social activity supported by virtual agents - Bönsch, Andrea; Ehret, Jonathan; Rupp, Daniel; Kuhlen, Torsten W. (Frontiers in Virtual Reality, 2024)
Effective navigation and interaction within immersive virtual environments rely on thorough scene exploration. Therefore, wayfinding is essential, assisting users in comprehending their surroundings, planning routes, and making informed decisions. Based on real-life observations, wayfinding is, thereby, not only a cognitive process but also a social activity profoundly influenced by the presence and behaviors of others. In virtual environments, these 'others' are virtual agents (VAs), defined as anthropomorphic computer-controlled characters, who enliven the environment and can serve as background characters or direct interaction partners. However, little research has been done to explore how to efficiently use VAs as social wayfinding support. In this paper, we aim to assess and contrast user experience, user comfort, and the acquisition of scene knowledge through a between-subjects study involving n = 60 participants across three distinct wayfinding conditions in one slightly populated urban environment: (i) unsupported wayfinding, (ii) strong social wayfinding using a virtual supporter who incorporates guiding and accompanying elements while directly impacting the participants' wayfinding decisions, and (iii) weak social wayfinding using flows of VAs that subtly influence the participants' wayfinding decisions by their locomotion behavior. Our work is the first to compare the impact of VAs' behavior in virtual reality on users' scene exploration, including spatial awareness, scene comprehension, and comfort. The results show the general utility of social wayfinding support, while underscoring the superiority of the strong type. Nevertheless, further exploration of weak social wayfinding as a promising technique is needed. Thus, our work contributes to the enhancement of VAs as advanced user interfaces, increasing user acceptance and usability.